The Influence of Suggestion on Suicide: Substantive and Theoretical Implications of the Werther Effect - Phillips, David P. (American Sociological Review, 1974)
This paper shows that suicides increase immediately after a suicide story has been publicized in the newspapers in Britain and in the United States, 1947-1968. The more publicity devoted to a suicide story, the larger the rise in suicides thereafter. The rise in suicides after a story is restricted mainly to the area in which the story was publicized. Alternative explanations of these findings are examined; the evidence indicates that the rise in suicides is due to the influence of suggestion on suicide, an influence not previously demonstrated on the national level of suicides. The substantive, theoretical, and methodological implications of these findings are examined.